PENGARUH TINGKAT PENDIDIKAN, PENGETAHUAN AKUNTANSI, UMUR USAHA DAN SKALA USAHA PELAKU USAHA MIKRO KECIL DAN MENENGAH (UMKM) TERHADAP PENGGUNAAN INFORMASI AKUNTANSI DI KECAMATAN SENAPELAN - Karin; Abrar (Journal Of Islamic Finance And Accounting Research, 2022)
This study aims to determine the effect of education level, accounting knowledge, business age and business scale of micro, small and medium enterprises (MSMEs) on the use of accounting information in Senapelan District. The method used in this research is simple random sampling. The type of data used is primary data. Data collection carried out in this study is the distribution of questionnaires. The sample of this study consisted of 74 businesses. Data processing was carried out using SPSS version 21 program tools. The research model used by the researcher was multiple linear regression analysis. Based on the results of the tests carried out, it was concluded that the level of education, accounting knowledge, business age and business scale had a significant effect on the use of accounting information on MSMEs in Senapelan District.